2009
DOI: 10.2478/s11772-008-0066-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of quantum dots shape approximation on size reconstructed from atomic force microscopy measurements

Abstract: In this work we discuss the influence of the atomic force microscopy (AFM) probe tip geometry and the object — quantum dot form on the quantum dots dimension in the growth plane reconstructed from the AFM measurements. It is shown that ignoring the geometry of the probe tip and the quantum dot leads to significant differences between dimensions obtained from the AFM measurements and the real dimensions. Inaccuracies in QD size determination of the nano-objects from AFM measurements are defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The measurements of the QD heights and diameters gave average values of 4.3±0.1 and 24±0.5 nm, henceforth the aspect ratio was about 0.18. Nevertheless, the resolution of AFM is limited by the sharpness and shape of the tip whose normal radius of curvature is 10-60 nm [20,21] and there is a lack of precision in AFM measurements of nanometer-sized samples in the lateral dimension [22]. In order to obtain trustworthy spatial measurements of QD diameters, cross sectional TEM images were taken along [110] zone axis at the sample surface.…”
Section: Resultsmentioning
confidence: 99%
“…The measurements of the QD heights and diameters gave average values of 4.3±0.1 and 24±0.5 nm, henceforth the aspect ratio was about 0.18. Nevertheless, the resolution of AFM is limited by the sharpness and shape of the tip whose normal radius of curvature is 10-60 nm [20,21] and there is a lack of precision in AFM measurements of nanometer-sized samples in the lateral dimension [22]. In order to obtain trustworthy spatial measurements of QD diameters, cross sectional TEM images were taken along [110] zone axis at the sample surface.…”
Section: Resultsmentioning
confidence: 99%
“…Since AFM images are a convolution of the probe tip and the QD itself, the measured widths can be $8-10 nm larger than the actual diameters of the QDs. 25,26 To minimize tip-induced differences in comparing the island sizes and densities, all the samples in this study were scanned using the same AFM tip, and tip broadening was not observed after extensive scanning. It should be noted that the dimensions of the buried QDs will be different from those of the uncapped QDs that are presented here; unlike the surface QDs, buried QD dimensions are influenced by surface segregation of the In atoms and alloying of the InAs in the QD with the surrounding GaAs.…”
mentioning
confidence: 99%
“…The tip was TESP SS type from Bruker, which has a radius of about 2 nm. After introduction correction of measured diameter (D), the height (h) of the measured object and the tip radius (R) [13] according to Eq. (1), the average diameter (d) was accepted as 28 nm.…”
Section: Particles Analysismentioning
confidence: 99%